'It is not a quick fix' structural and contextual issues that affect implementation of integrated health and well-being services: a qualitative study from North East England. (November 2017) - Cheetham, M.; Visram, S.; Rushmer, R.; Greig, G.; Gibson, E.; Khazaeli, B.; Wiseman, A.
Abstract: Objective: The objective of this article is to examine the factors affecting the design, commissioning and delivery of integrated health and well-being services (IHWSs), which seek to address multiple health-related behaviours, improve well-being and tackle health inequalities using holistic approaches. Study design: Qualitative studies embedded within iterative process evaluations. Methods: Semi-structured interviews conducted with 16 key informants as part of two separate evaluations of IHWSs in North East England, supplemented by informal observations of service delivery. Transcripts and fieldnotes were analysed thematically. Results: The study findings identify a challenging organisational context in which to implement innovative service redesign, as a result of budget cuts and changes in NHS and local authority capacity. Pressures to demonstrate outcomes affected the ability to negotiate the practicalities of joint working. Progress is at risk of being undermined by pressures to disinvest before the long-term benefits to population health and well-being are realised. The findings raise important questions about contract management and relationships between commissioners and providers involved in implementing these new ways of working. Conclusions: These findings provide useful learning in terms of the delivery and commissioning of similar IHWSs, contributing to understanding of the benefits and challenges of this model of working. Highlights: Single-issue lifestyle services have made little impact on health inequalities. Evidence is limited on the practicalities of implementing integrated health and well-being services. Adverse structural and contextual factors risk destabilising these fledgling services. Progress has been undermined by ongoing austerity and cuts to public health budgets. Commissioners require robust, timely evidence of impact that takes into account the needs of the target communities.